Mass-spectrometer diagnostics complex with cryogenic nitrogen trap - Tsybenko, S.A.; Kramskoj, E.D.; Korovin, V.B.; Yevsyukov, A.V.; Lozin, A.V.; Moiseenko, V.E.; Kholomyeyev, G.A.; Gribanov, V.Yu.; Kozulya, M.M.; Maznichenko, S.M.; Krasyuk, A.Yu.; Baron, D.I.; et al. (Вопросы атомной науки и техники, 2019)
The measuring complex with the cryogenic nitrogen trap [1] was created to monitor the gas composition in the stellarator Uragan-2M chamber. The complex provides several gas sampling options for the research: directly from the vacuum chamber, and condensed gas from the cryogenic trap chamber after its being heated. A new measuring cryogenic trap with its own valves was developed to implement the second method. It is necessary to provide such a state of the internal vacuum surfaces of the complex so that the background gas emission from the walls of the measuring vacuum chamber does not lead to the measurement errors in order to obtain more accurate mass spectral data. The heating of the chamber walls and continuous RF discharge at frequencies of 6…8 MHz and the power of 1 kW without a magnetic field was planned to used for this purpose. Two RF antennas, rod and planar, were designed. На стелараторі Ураган-2М був створений діагностичний комплекс з криогенною азотною пасткою [1] для контролю складу газу в камері стеларатора. Комплекс передбачає декілька варіантів відбору проб газу для дослідження: безпосередньо з вакуумної камери та конденсованого газу з камери криогенної пастки після її нагрівання. Для реалізації другого методу була розроблена нова вимірювальна криогенна пастка з власними клапанами. Для отримання точніших мас-спектральних даних необхідно забезпечити такий стан внутрішніх вакуумних поверхонь комплексу, щоб витік фонового газу зі стінок вимірювальної вакуумної камери не призвів до помилок у вимірах. Для цього планувалося нагрівання стін камери та безперервного ВЧ-розряду на частотах близько 6…8 МГц потужністю до 1 кВт без магнітного поля. Були розроблені дві ВЧ-антени: штирьова і пластинчата. На стеллараторе Ураган-2М был создан диагностический комплекс с криогенной азотной ловушкой [1] для контроля состава газа в камере стелларатора. Комплекс предусматривает несколько вариантов отбора проб газа для исследования: непосредственно с вакуумной камеры и конденсированного газа из камеры криогенной ловушки после её нагрева. Для реализации второго метода была разработана новая измерительная криогенная ловушка со своими клапанами. Для получения более точных масс-спектральных данных необходимо обеспечить такое положение внутренних вакуумных поверхностей комплекса, чтобы утечка фонового газа со стенок измерительной вакуумной камеры не привела к ошибкам в измерениях. Для этого планировался нагрев стен камеры и непрерывного ВЧ-разряда на частотах порядка 6…8 МГц мощностью до 1 кВт без магнитного поля. Были разработаны две ВЧ-антенны: штыревая и пластинчатая.